Crossing borders: the PACK experience of spreading a complex health system intervention across low-income and middle-income countries. (26th October 2018) - Cornick, Ruth; Wattrus, Camilla; Eastman, Tracy; Ras, Christy Joy; Awotiwon, Ajibola; Anderson, Lauren; Bateman, Eric; Zepeda, Jorge; Zwarenstein, Merrick; Doherty, Tanya; Fairall, Lara
Abstract : Developing a health system intervention that helps to improve primary care in a low-income and middle-income country (LMIC) is a considerable challenge; finding ways to spread that intervention to other LMICs is another. The Practical Approach to Care Kit (PACK) programme is a complex health system intervention that has been developed and adopted as policy in South Africa to improve and standardise primary care delivery. We have successfully spread PACK to several other LMICs, including Botswana, Brazil, Nigeria and Ethiopia. This paper describes our experiences of localising and implementing PACK in these countries, and our evolving mentorship model of localisation that entails our unit providing mentorship support to an in-country team to ensure that the programme is tailored to local resource constraints, burden of disease and on-the-ground realities. The iterative nature of the model's development meant that with each country experience, we could refine both the mentorship package and the programme itself with lessons from one country applied to the next—a 'learning health system' with global reach. While not yet formally evaluated, we appear to have created a feasible model for taking our health system intervention across more borders.